Fabrication of graded Porous Hydroxyapatite by using coconut fibre - Ahmad Kasyfullah, Arifin (Universiti Malaysia Perlis, 2009)
This study was carried out to develop sample hydorxyapatite (HA) cylindrical with have porous in particular part for example his external layers has solid part while on the inside it exist porous. Further it can make as bone implant for the compact bone part and spongy bone. Hydroxyapatite (HA) in the form of powder mixed with coconut fibre along with Polyethlytene Glycol (PEG) which is used as binder. Mixing process of the raw material using milling machine for 16 hours with the constant speed to make sure the mixture mixed homogenous. The slurry mixture of the HA then pouring in the cylindrical mould and leaves it dry before sintering. The sample was sintered at 1200°C in air atmosphere. The testing and characterization of sample was done such as Particle size analysis, X-Ray analysis, SEM dan compression test. From this study it show that the sample have shrinkage 35.45 %, density 1.74 (g/cm3), porosity 58.89 and compressive strength 4.124 Mpa . This results shows that a sample with porous gradient like human cancellous bone and compact bone can be produce by using slip casting technique and using coconut fibre as the porosifier agent.